Informativity in Ibn Zaydūn's Sīniyyah - Alsarhan, Abdullah E. (Dirasat: Human and Social Sciences, 2024)
Objective: This research aims to develop an approach for informativity- a text analysis criterion established by De Beaugrande and Dressler - by applying it to Ibn Zaydūn's Sīniyyah. This shall motivate its application to Arabic poetry, namely classical Arabic poetry, to demonstrate the poet's ability to manoeuvre within the conditions and limitations of language to convey the desired informativity and stimulate recipient interaction. Methods: The study employs an analytical approach that is based on prosody and rhetoric on Ibn Zaydūn's Sīniyya. The Sīniyyah follows a specific prosodical scheme, i.e. majzūʾ al-ramal, with the rhyme ‘sīn’ connected by ‘alif’ followed by ‘wāw’ Consequently, these limited options diminished the ability to manoeuvre the informativity level through increasing and decreasing. To achieve the desired results, the study traces the syntax leading to the rhyme in each verse. At the end of each verse, the informativity degree variation, whether increasing or decreasing, was examined, and justified. Results: The study finds that Ibn Zaydūn maintains the second level of informativity throughout the poem by balancing between syntactic structures that reflect the first level of informativity and increased by rhetorical techniques. The informativity is further increased to the second level by forming expected semantic units in syntactic forms, as evident in every verse of the poem, except for the second verse which further increased to the third level, and the last verse that serves as a concluding signature of a letter sent to Ibn Burd al-Asghar. Conclusions: This research highlights the need for further applications of informativity in Arabic, especially in classical poetry, to explore the specific attributions of the Arabic language, its poetry, and its linguistic and literary limitations, such as rhyme and metre, that Arabic authors implement to achieve the desired level of informativity.